Peter Grzybek (November 22, 1957–May 29, 2019): In memoriam - Mieder, Wolfgang (Slavia Centralis, 2020)
The author describes the life and work of the late German linguist Peter Grzybek, who had a tremendous influence on the multifaceted study of proverbs.